Incorporating cultural design elements in mobile applications creative industries in Malaysia: a conceptual study - Muhammad Zulhilmi Samsuri (Tanjong Malim, 2021)
Incorporating cultural design elements in mobile applications creative industries in Malaysia: a conceptual study by Muhammad Zulhilmi Samsuri